Family education and decisive participation in schools. Overcoming barriers to community involvement in school (Journal of Parents and Teachers, 2016)
This article focuses on the modalities of family involvement in learning communities. For this purpose, it describes the successful educational actions that are contributing to overcome the barriers that often hinder the participation of families and the community in schools. Particularly, we highlight educational and decisive participation and the impact derived from these forms of community involvement.
Keywords: Decisive participation; educational participation; learning communities; family education; community involvement.